2018
DOI: 10.48550/arxiv.1810.10001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDEs on deformable domains: Boundary Arbitrary Lagrangian-Eulerian (BALE) and Deformable Boundary Perturbation (DBP) methods

Javier Rivero-Rodriguez,
Miguel Perez-Saborid,
Benoit Scheid

Abstract: Many physical problems can be modelled by partial differential equations on unknown domains. Several examples can easily be found in the dynamics of free interfaces in fluid dynamics, solid mechanics or in fluid-solid interactions. To solve these equations in an arbitrary domain with nonlinear deformations, we propose a mathematical approach allowing to track the boundary of the domain, analogue of, and complementary to, the Arbitrary Lagrangian-Eulerian (ALE) method for the interior of the domain. We name thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In addition, the mesh was symmetrical with respect to x = 0 and the skewness of the mesh was always around 0.93 to ensure a good mesh quality. The steady results were verified by comparing the numerical solution with the theoretical unidirectional flow solution given above in (2.13) and (2.14) and with the results given by Rivero-Rodriguez, Perez-Saborid & Scheid (2018).…”
Section: Numerical Methods and Stability Of The Interfacementioning
confidence: 53%
“…In addition, the mesh was symmetrical with respect to x = 0 and the skewness of the mesh was always around 0.93 to ensure a good mesh quality. The steady results were verified by comparing the numerical solution with the theoretical unidirectional flow solution given above in (2.13) and (2.14) and with the results given by Rivero-Rodriguez, Perez-Saborid & Scheid (2018).…”
Section: Numerical Methods and Stability Of The Interfacementioning
confidence: 53%
“…Consequently, the boundary conditions (2.3), (2.4a) and (2.4b) cannot be imposed explicitly. To circumvent this difficulty, we followed the methodology developed by Rivero-Rodriguez, Perez-Saborid & Scheid (2018) to write these boundary conditions referred to the unperturbed particle's position x p,0 . This process resulted in (B3), ( B5) and (B6), respectively, as outlined in detail in Appendix B.…”
Section: Boundary Conditions Of the Stability Problemmentioning
confidence: 99%
“…Note that the jet breaking is intrinsically transient as it results from the Rayleigh-Plateau instability but the droplet generation, as mentioned above, can be quasi-static in the limit of low dispersed flow rate. Van Brummelen et al [42] having shown that solving the transient Navier-Stokes equation to obtain the steady solution is often inefficient, Rivero-Rodriguez et al [43] have developed the Boundary Arbitrary Lagrangian-Eulerian (BALE) method to facilitate the solution of steady Navier-Stokes equations with free surfaces. Rivero-Rodriguez and Scheid [44,45] have then applied this method to study the dynamics of deformable and off-centered bubbles in microchannels, allowing for exhaustive parametric analysis, taking the advantage of continuation methods suitable for tracking stationary solutions.…”
Section: Introductionmentioning
confidence: 99%